Increase in T helper type 17 cells in children with Kawasaki disease is NR4A2 dependent. (26th March 2018) - Zhang, Kuo; Li, Zhengmin; Li, Meng; Zhang, Yingqi; Wu, Shouzhen; Chen, Chao
The aim of this study was to evaluate the relationship between T helper type 17 (Th17) cells and Kawasaki disease (KD). Flow cytometry results showed that the number of Th17 cells in the peripheral blood mononuclear cells (PBMCs) of KD patients was significantly elevated. Enzyme-linked immunosorbent assay (ELISA) results showed that the serum concentrations of two Th17 cytokines, interleukin (IL)-17 and IL-6, were significantly increased in KD patients. In addition, real-time quantitative polymerase chain reaction (PCR) results showed that the messenger RNA (mRNA) expression of two molecules related to Th17 cell differentiation, retinoic acid–related orphan receptor C (RORC) and NR4A2, was upregulated in the CD4+ T cells of KD patients. Intravenous immunoglobulin (IVIG) infusion significantly reduced the proportion of Th17 cells, decreased serum concentrations of IL-7 and IL-6, and lowered the mRNA levels of RORC and NR4A2 in IVIG treatment–sensitive KD patients. Finally, the results of a Pearson's correlation analysis illustrated that IL-17 mRNA levels in CD4+ T cells of KD patients were positively correlated with NR4A2 but not RORC mRNA expression. Our results demonstrate that Th17 cells play an important role in KD development and IVIG treatment and that Th17 cells and IL-17 may be used as markers for the occurrence of KD or as treatment targets for KD therapies. In addition, our results suggest that the underlying mechanism of IL-17 production in KD is NR4A2 dependent.